The Role of TikTok Content Virality in Shaping Gen Z’s Purchase Intentions - Lesmana, Alvin (SAFE-Network, 2025)
The rapid growth of social media, particularly TikTok, has reshaped marketing communication and consumer behavior, especially among Generation Z (Gen Z). This study aims to examine the role of TikTok content virality in shaping Gen Z’s purchase intentions in Pontianak City. A quantitative survey approach was employed with 225 Gen Z respondents who had been active TikTok users for at least the past six months. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. The findings indicate that TikTok content virality significantly influences Gen Z’s purchase intentions, both directly and indirectly through mediating variables: user engagement, emotional response, and trust/credibility. Furthermore, the moderation analysis reveals that brand trust and influencer credibility strengthen the relationship between content virality and purchase intentions. This suggests that the effectiveness of viral content is determined not only by its reach but also by the degree of consumer trust in both the brand and the content creator. Theoretically, this research contributes to digital marketing literature by reinforcing the Stimulus-Organism-Response (SOR) model and the Theory of Planned Behavior (TPB) within the TikTok marketing context. Practically, it provides valuable insights for marketers to design authentic, interactive, and credible content that sustainably enhances Gen Z’s purchase intentions.